An examination of digital empathy: When farmers speak for the climate through TikTok - İlkay Unay-Gailhard; Kati Lawson; Mark A. Brennan (Journal of Rural Studies, 2023)
Food production contributes to and is affected by climate change. With this dual-sided nature of food production, separate from policymakers, the media, scientists, and activists, how climate dialogue engagement occurs when farmers speak about climate is the interest of this research. Due to the important role of youth in climate activism, we analyze climate dialogue engagement on the youthful platform of TikTok during the most recent United Nations COP26 meeting, when climate dialogues peaked globally in the media. This study includes a two-step analyses: Step-I involved a post-focused analysis investigating digital empathy surrounding TikTok posts created by farmers. Step-II was a user-focused analysis exploring TikTok farmers' perspectives on the public engagement with their climate-farming related posts. The results suggest that the typical empathic engagement of the analyzed climate dialogue is emotional reactions (expressed briefly or explicitly). Even though the analyzed videos contain alternative ways of communication (dynamic demonstrations, humor), cognitive empathy can differ based on the narrative and narrator. These findings contribute to studies investigating the outcome of climate communication among communities that share specific interests, elaborating on the role of alternative ways of communication in climate dialogues, and exploring how digital empathy serves to break down self-silencing among farmers and the online communities that they reach out to.
Keywords: 630; digital empathy; young farmers; online dialogue engagement; climate change dialogue; food system communication; TikTok; UN COP26